Molecular basis of carrageenan-induced cytokines production in macrophages - Lopes, Alexandre H.; Silva, Rangel L.; Fonseca, Miriam D.; Gomes, Francisco I.; Maganin, Alexandre G.; Ribeiro, Lucas S.; Marques, Lucas Maciel Mauriz; Cunha, Fernando Q.; Alves-Filho, Jose C.; Zamboni, Dario S.; Lopes, Norberto P.; Franklin, Bernardo S.; et al. (Cell communication and signaling, 2020)
Background Low molecular weight carrageenan (Cg) is a seaweed-derived sulfated polysaccharide widely used as inflammatory stimulus in preclinical studies. However, the molecular mechanisms of Cg-induced inflammation are not fully elucidated. The present study aimed to investigate the molecular basis involved in Cg-induced macrophages activation and cytokines production. Methods Primary culture of mouse peritoneal macrophages were stimulated with Kappa Cg. The supernatant and cell lysate were used for ELISA, western blotting, immunofluorescence. Cg-induced mouse colitis was also developed . Results Here we show that Cg activates peritoneal macrophages to produce pro-inflammatory cytokines such as TNF and IL-1β. While Cg-induced TNF production/secretion depends on TLR4/MyD88 signaling, the production of pro-IL-1β relies on TLR4/TRIF/SYK/reactive oxygen species (ROS) signaling pathway. The maturation of pro-IL1β into IL-1β is dependent on canonical NLRP3 inflammasome activation via Pannexin-1/P2X7/K + efflux signaling. In vivo, Cg-induced colitis was reduced in mice in the absence of NLRP3 inflammasome components. Conclusions In conclusion, we unravel a critical role of the NLRP3 inflammasome in Cg-induced pro-inflammatory cytokines production and colitis, which is an important discovery on the pro-inflammatory properties of this sulfated polysaccharide for pre-clinical studies. 1e-L4pWBc1sacKrQDF6Cf5 Video abstract Graphical Abstract Carrageenan (Cg) is one the most used flogistic stimulus in preclinical studies. Nevertheless, the molecular basis of Cg-induced inflammation is not totally elucidated. Herein, Lopes et al. unraveled the molecular basis for Cg-induced macrophages production of biological active IL-1β. The Cg-stimulated macrophages produces pro-IL-1β depends on TLR4/TRIF/Syk/ROS, whereas its processing into mature IL-1β is dependent on the canonical NLRP3 inflammasome.